Sweet gifts from the New World: Indian foods in the medicinal recipes of Father Bernabé Cobo (17th century) - Varella, Alexandre C. (2009)
Bernabé Cobo writes various recipes to eat the products of the New World, including his life experience in America during the first half of the 17th century. The criterion of the temperance of sweet and sour flavors, and particularly the use of sugar, become central to a healthy diet and medication with fruits and tubers in beverages prepared with native herbs. They are recipes to correct aspects of wild nature or oppose the uses and customs of the barbarians, negative signs in the speech of authority of the Spanish. But they are immersed in a new world of intercultural practices, while Father Cobo searches for connections and finds concordances with indigenous habits. In all this, the sweet recipes can hint at vices of the Spanish in the New World, as the historian Cobo demonstrates.